O Programa de Regionalização do Turismo no Brasil e a competitividade espacial - Maria Aparecida Pontes da Fonseca; Carolina Todesco; Rodrigo Cardoso da Silva (Confins)
The Tourism Regionalization Program (PRT) completes 16 years of implementation and in this period has shown significant changes with the increase in the number of tourist regions, at the same time as the decrease in the number of municipalities in those regions. The objective of this work is to analyze the guidelines for the process of tourism regionalization implemented by the Ministry of Tourism in Brazil. The research methodology is based on a bibliographic and documentary study, having as main source the ministerial ordinances and the editions of the Brazilian Tourism Map. The results indicate that the fragility of the criteria for the composition of tourist regions and the categorization of municipalities constitute an obstacle to greater success of this public policy. The guideline of the PRT is the competitiveness that has been inducing spatial selectivity within the scope of the program through the categorization of municipalities and the proliferation of tourist regions in search of greater identity to the tourist product offered. Thus, the PRT stimulates both interregional competitiveness and intra-regional competition.